Rethinking “surplus populations”: theory from the peripheries - Cowan, Tom (2024)
Critical scholarship on twenty-first century capitalist development has called attention to certain structural limits on employment growth. Large populations excluded from formal employment are seen to eke out a precarious subsistence in informal economies, seemingly “surplus” to the needs of capital. This article, by contrast, aims to recast labor in the “peripheries,” not as an externalized quantity redundant to emerging economic formations, but rather as integral if of-ten hidden features of capitalist value extraction. Rethinking, in this way, “surplus populations,” we argue for particular attention to the heterogeneity of contemporary capitalist labor arrangements and to associated patterns of ideological de-valuation, which underpin capitalist markets in the South and East as well as in peripheralized spaces in the North and West.